Sustainable Finance in Financing Plantation Companies by Banking : Case Study of Palm Oil Corporation in Donggala Central Sulawesi Tengah - Rosalina, Linda; Kartodiharjo, Hariadi; Sudjito, Arie (Jurnal Pengelolaan Sumberdaya Alam dan Lingkungan (Journal of Natural Resources and Environmental Management), 2023)
Sustainable finance is a form of financing provided by Financial Institutions (FIs) to debtors by considering sustainability aspects into their decisions. Sustainable finance has not become a serious concern and orientation of FIs in providing credit or financing to debtors. Problem financing reflects the problem of two conflicting economic actors (agency). By conducting an analysis of sustainable financial performance and agency relationship analysis, this study shows that assessing the sustainability performance of a company (the debtor) required detail criteria and indicators of sustainable finance. When disbursing credit, banks cannot only look at the financial health and stability of a company. This is because companies that already have sustainability certification and fulfill administrative aspects still have unresolved Environmental, Social and Governance (ESG) issues. The involvement of the parties in building an “Information Hub” (coordination forum) related to ESG practices centered in the regions is important.